Legal Protection for Buyers of Inherited Land Who Have Not Been Certified In Islamic Law - Masriani, Yulies Tiena (JURNAL USM LAW REVIEW, 2024)
The urgent need for legal protection for buyers of uncertified inherited land under Islamic law is critical. This study employs a normative juridical approach, supported by an extensive literature review, to examine the complexities of buying and selling inherited land within the framework of Islamic inheritance law, known as farāid. This system delineates specific shares for each heir as guided by syara'. The process of purchasing inherited land mirrors that of individual land transactions, with significant distinctions concerning certification status. Key findings reveal that all heirs listed on the Heir Certificate, issued by the District Head or Notary, must consent to any sale. If the seller is later found to lack rightful ownership or if the documentation is fraudulent, a buyer acting in good faith is entitled to legal protection. This framework safeguards buyers from potential legal repercussions stemming from the seller's misrepresentation or lack of ownership. The study underscores the necessity for robust legal frameworks to protect buyers and uphold justice in land transactions, particularly in situations where certification is absent. This research analyzes the legal protections available to buyers of uncertified inherited land, emphasizing the importance of awareness and due diligence in transactions to mitigate risks associated with unclear legal aspects.